Viscosity Measurement of Blended Patchouli Oil at Atmospheric Pressure and Room Temperature - Yusibani, Elin; Woodfield, Peter Lloyd; Ardiah, Lena; Surbakti, Muhammad Syukri; Rahmi, Rahmi (ITB Journal Publisher, LPPM ITB, 2019)
Patchouli is an essential oil used in perfumes, cosmetics, soaps, insect repellents and also a candidate for biodiesel from non-edible oil. Patchouli oil from Aceh Province, Indonesia, is generally produced using a distillation process. The relationships between physical properties, i.e. the viscosity and quality, of patchouli oil from Aceh Province and blends with other oils, were investigated. The mixture oils used were palm oil, kerosene and lubricant oil SAE 40. The mixture compositions were 100:0; 75:25; 50:50; 25:75 and 0:100 (v/v). It was found that mixing palm crude oil (25%) or lubricant oil (25%) with patchouli oil increased the viscosity by about 41% and 72%, respectively, compared with pure patchouli oil. A 53% decrease in viscosity was observed when the patchouli oil blend contained 25% kerosene. Natural variation in patchouli alcohol (PA) and iron (Fe) content in the patchouli oil sample was found to increase the value of viscosity by up to 1.5%.